Discrepancies in International Data: An Application to China–Hong Kong Entrepôt Trade - Feenstra, Robert C; Hai, Wen; Woo, Wing T; Yao, Shunli (American Economic Review, 1999)
Discrepancies in International Data: An Application to China-Hong Kong Entrepot Trade by Robert C. Feenstra, Wen Hai, Wing T. Woo and Shunli Yao. Published in volume 89, issue 2, pages 338-343 of American Economic Review, May 1999